KOMUNIKASI PERSUASIF DALAM NEGOSIASI BISNIS RADIO KIS SEMARANG - Usaid Abdullah Dzikri; wiwid Noor Rakhmad; Adi Nugroho (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
The radio industry is currently experiencing a downward trend, causing the number of radio listeners to decrease and spending on radio advertising to decrease. However, KIS Radio a Catholic-based radio in Semarang manages to get around ten advertisers a month. That's quite a lot in the midst of a sluggish radio industry. This research aims to describe how persuasive communication is used by KIS Radio in business negotiations to get advertisers, using a qualitative descriptive research method with a case study approach. In this research, the data collection technique used was interviewed, with the Miles and Huberman Model data analysis technique. The theories used in this research are the Motivated Sequence theory and Lawrence Kincaid's negotiation communication model. The research results show that the Radio KIS marketing team carries out persuasive communication to potential advertisers using the Motivated Sequence theory by focusing on satisfaction, where in this step the marketing team tries to provide satisfactory solutions, fulfill the needs and solve the problems of potential advertisers. The application of this Motivated Sequence makes KIS Radio's persuasive marketing messages more argumentative and more convincing for potential advertisers to advertise on KIS Radio. Likewise, in negotiations, the Radio KIS marketing team uses Lawrence Kincaid's communication model, where Radio KIS marketing attempts to persuade potential advertisers and also tries to understand the desires and needs of potential advertisers, and also provides various alternative solutions that are tailored to the needs and business situations experienced by the candidate. advertisers, so that both parties can reach a mutual agreement which is the goal of business negotiations, so that the interests of both parties can be fulfilled.